INCREASING PEDAGOGIC COMPETENCY AND PROFESSIONAL COMPETENCY THROUGH EDUCATION AND TRAINING DEVELOPMENT OF SUSTAINABLEPROFESSION OF DEVELOPMENT (Case Study of Kindergarten Teachers in Bandung) - Rita Nurunnisa (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
ABSTRACTTeacher competence is the teacher's capital in carrying out the main task and its function in educating the students. There are 4 competencies that must be possessed by teachers, namely, pedagogic competence, professional competence, personality competence and social competence. Teachers should have awareness in themselves to continue to learn and develop themselves continuously in an effort to improve services to learners. One of the teacher's efforts in self-development is through education and training. For that, the authors examine the "How education and training Sustainable Development of Keprofesian in improving the pedagogic and professional competence of kindergarten teachers in Bandung?" Where pedagogic competence and professional competence are both mutually integrated and can not be separated. This study aims to describe the process of planning, implementation, assessment and results and the impact of education and training on teacher performance through descriptive and qualitative approaches. The results of this study indicate through education and training program Sustainable Development of Keprofesian in Bandung value Competency Teacher Test average increased significantly and in accordance with the expected minimum achievement criteria. In addition, teachers also feel an increase in knowledge, variations of learning fun to apply to learners and implement sustainable self-development plans.